Relationships Family Support And Quality of Life Patient Chronic Kidney Disease With Haemodialysis Therapy in Sanglah Denpasar Hospital. - Siska Aristia Handayani (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Patients with chronic kidney disease who undergo haemodialysis will experience physiological and psychological problems. A variety of psychological problems experienced will affect the physical condition of the patient and tends to result in a worse quality of patients’s life. This study aims to analyze the relationship of family support and the quality of life patients with chronic kidney disease undergoing haemodialysis therapy in Sanglah Denpasar Hospital. Types of research is descriptive correlational cross – sectional approach. Data collection using purpose sampling techniques from 50 respondents. Data collection instruments with guidance of Family Support and KDQOL (Kidney Disease Quality of Life) questionnaires. The study found that most respondents (60%) have a good family support and data about the quality of life for the majority of respondents (70%) have a good quality of life. The results of the Rank Spearman Rho correlation test (p ? 0.05), p value = 0,000 a=0,05 and r = 0,854, meaning there is a correlation or strong relationship between family support and quality of life of patients with chronic kidney disease undergoing hemodialysis. It recommended to health workers, especially nurses to optimize family support for patients with chronic kidney disease undergoing haemodialysis therapy.